2017
DOI: 10.1088/1674-1056/26/2/027303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coupling geometry on thermoelectric properties of oligophenyl-base transistor

Abstract: Thermal and electron transport through organic molecules attached to three-dimensional gold electrodes in two different configurations, namely para and meta with thiol-terminated junctions is studied theoretically in the linear response regime using Green's function formalism. We used thiol-terminated (-SH bond) benzene units and found a positive thermopower because the highest occupied molecular orbital (HOMO) is near the Fermi energy level. We investigated the influence of molecular length and molecular junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…According to the ZT formula, if we consider phonon thermal conductance, κ ph , the figure of merit is decreased while effect of phonons is important at high temperature. On the other hand, in the case of connecting a molecule to the electrode, the phonon thermal conductivity is very small and it can be ignored [66][67][68][69][70] . Figure 10d indicates that for the Au-Fe@C 20 -Au system the figure of merit around the Fermi level is bigger than that of for Au-C 20 -Au system.…”
Section: Resultsmentioning
confidence: 99%
“…According to the ZT formula, if we consider phonon thermal conductance, κ ph , the figure of merit is decreased while effect of phonons is important at high temperature. On the other hand, in the case of connecting a molecule to the electrode, the phonon thermal conductivity is very small and it can be ignored [66][67][68][69][70] . Figure 10d indicates that for the Au-Fe@C 20 -Au system the figure of merit around the Fermi level is bigger than that of for Au-C 20 -Au system.…”
Section: Resultsmentioning
confidence: 99%
“…, γ L/R is the coupling strength between the molecule and the electrodes (here we assumed γ L = γ R = γ), and r s L=R is the DOS of the left (L) or right (R) electrode in terms of the spin σ which is independent of the applied voltage and energy in the WB approximation used in this study. The DOS for the spin-up and spin-down states of the cobalt electrodes were chosen as ρ" = 0.5772 1/eV and ρ# = 0.1367 1/eV, respectively [45].…”
Section: Magnetic Tunnel Junction Modelmentioning
confidence: 99%
“…Then, in the second part we considered a single-molecule MTJ comprising a phenyl dithiol (PDT) molecule or a biphenyl dithiol (BPDT) molecule connected to two ferromagnetic (FM) cobalt electrodes mediated by a sulfur anchoring unit and inspected current-voltage characteristics and conductance using the non-equilibrium Green's function (NEGF) formalism. PDT and BPDT molecules are aromatic organic compounds characterized with π orbitals suggesting that they are suitable candidates for transport studies [45]. To test our idea regarding the qualitative similarity between the neuron system and MTJ, we introduced an effective spinpolarized tunneling conductance, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several studies explored the effect of structural or chemical modification on the thermoelectric properties of molecular junctions by manipulating their transport properties. For example, it has been shown that the length of the molecule [14][15][16][17], functionalization of the molecule with side groups [18][19][20][21], intervention of anchoring groups [22][23][24], molecule-electrode coupling geometry [25,26] and impurity doping [7,27] can significantly tune the conductance, thermopower and figure of merit of molecular junctions, depending on the system. In this context, a key factor in the regulation of transport properties of metal-molecule-metal structures is the energy level alignment between Frontier molecular orbitals (FMOs) and the Fermi level of electrodes [28,29] that can be modulated, e.g., by the geometric position or charge transfer nature of anchoring groups [24,30,31] or side groups [20,21].…”
Section: Introductionmentioning
confidence: 99%